Validating 1-Year Reliable Change Methods. (3rd September 2020) - Hammers, Dustin B; Porter, Sariah; Dixon, Ava; Suhrie, Kayla R; Duff, Kevin
Abstract: Objective: reliable change methods can assist in the determination of whether observed changes in performance are meaningful. The current study sought to validate previously published 1-year standardized regression-based (SRB) equations for commonly administered neuropsychological measures that incorporated baseline performances, demographics, and 1-week practice effects. Method: Duff et al.'s SRB prediction equations were applied to an independent sample of 70 community-dwelling older adults with either normal cognition or mild cognitive impairment, assessed at baseline, at 1 week, and at 1 year. Results: minimal improvements or declines were seen between observed baseline and observed 1-year follow-up scores, or between observed 1-year and predicted 1-year scores, on most measures. Relatedly, a high degree of predictive accuracy was observed between observed 1-year and predicted 1-year scores across cognitive measures in this repeated battery. Conclusions: these results, which validate Duff et al.'s SRB equations, will permit clinicians and researchers to have more confidence when predicting cognitive performance on these measures over 1 year.